Macro-Aspartate Aminotransferase and Its Laboratory Detection: A Case Report - Aleknavičiūtė-Valienė, Goda; Černiauskas, Linas; Riauka, Mantas; Vitkus, Dalius (Acta medica Lituanica, 2023)
Background. Increased enzyme activity in human blood serum is usually associated with the existence of disease. On the other hand, enzyme activity can also be elevated in the presence of benign conditions, such as macro-enzymes. Macro-enzymes could lead to highly unnecessary and invasive procedures which may cause complications to the patient and an extra cost for the hospital. Therefore, it is important to diagnose this condition in order to avoid unnecessary clinical tests. Case Presentation. We present a case of a 71-year-old asymptomatic female with persistent elevation of AST who was referred to our hospital for additional testing for underlying liver disease. By using polyethylene glycol (PEG) precipitation assay, we were able to identify macro-AST. This helped to avoid the high-risk liver biopsy procedure. Conclusion. In the case of an isolated elevation of AST activity with no clinical indications of liver disease, diagnostic work-up for macro-AST should always be considered by physicians.